Pengaruh Augmented Reality Marketing Terhadap Minat Beli Konsumen Melalui Customer Engagement pada Sephora di Indonesia - Lisdayanti, Annisa; Nilasari, Irma (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
This study analyzes the influence of Augmented Reality (AR) technology on consumer purchase intention with customer engagement as an intervening variable at Sephora Indonesia. This quantitative research involved 150 respondents who are users of Sephora Virtual Artist, analyzed using Structural Equation Modeling (SEM). The research instrument measures three main variables: Augmented Reality (interactivity, vividness, novelty), Customer Engagement (cognitive, emotional, behavioral), and Purchase Intention (intention, willingness, likelihood to purchase) using a five-point Likert scale. The research results show that AR has a positive and significant effect on customer engagement and purchase intention. Customer engagement also has a positive effect on purchase intention and is proven to mediate the relationship between AR and purchase intention. This study contributes to the AR literature in beauty e-commerce and recommends that Sephora optimize AR features, develop comprehensive customer engagement strategies, and continue investing in AR technology as a competitive advantage.